2017
DOI: 10.3945/jn.116.238485
|View full text |Cite
|
Sign up to set email alerts
|

Dairy Food Intake Is Inversely Associated with Risk of Hypertension: The Singapore Chinese Health Study

Abstract: Background: Epidemiological evidence from Western populations suggests that dairy food intake may reduce the risk of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 30 publications
0
12
1
1
Order By: Relevance
“…Four prospective studies were included in the meta-analysis for consumption of whole grains ( 24 27 ), 3 studies for refined grains ( 25 27 ), 8 for vegetables (6 reports) ( 27 32 ), 7 for fruits (5 reports) ( 27 , 28 , 30 32 ), 4 for nuts ( 27 , 33 35 ), 6 for legumes (4 reports) ( 27 , 28 , 34 , 36 ), 1 for eggs ( 34 ), 9 for dairy products ( 27 , 37 44 ), 8 for fish (6 reports) ( 27 , 34 , 38 , 45 47 ), 7 for red meat (5 reports) ( 34 , 38 , 45 , 48 , 49 ), 5 for processed meat (3 reports) ( 45 , 48 , 49 ), and 5 for SSBs (3 reports) ( 27 , 50 , 51 ) ( Supplemental Tables 2–13 ).…”
Section: Resultsmentioning
confidence: 99%
“…Four prospective studies were included in the meta-analysis for consumption of whole grains ( 24 27 ), 3 studies for refined grains ( 25 27 ), 8 for vegetables (6 reports) ( 27 32 ), 7 for fruits (5 reports) ( 27 , 28 , 30 32 ), 4 for nuts ( 27 , 33 35 ), 6 for legumes (4 reports) ( 27 , 28 , 34 , 36 ), 1 for eggs ( 34 ), 9 for dairy products ( 27 , 37 44 ), 8 for fish (6 reports) ( 27 , 34 , 38 , 45 47 ), 7 for red meat (5 reports) ( 34 , 38 , 45 , 48 , 49 ), 5 for processed meat (3 reports) ( 45 , 48 , 49 ), and 5 for SSBs (3 reports) ( 27 , 50 , 51 ) ( Supplemental Tables 2–13 ).…”
Section: Resultsmentioning
confidence: 99%
“…The enquiry about history of these diseases was made by asking if the participant has been told by a physician that he/she had any of these diseases in separate questions. Using standard protocols, separate studies validated the accuracy of the self‐reported diabetes mellitus8 and hypertension9 in this cohort. The robustness and accuracy of the self‐reported diabetes mellitus data were validated in a separate study analyzing 1651 cohort participants who reported history of diabetes mellitus at either baseline or follow‐up 1 interview, and 98.9% were confirmed by medical records or telephone interview 8…”
Section: Methodsmentioning
confidence: 87%
“…63 Additionally, during a follow-up interview conducted within the Singapore Chinese Health Study, 88% of the subjects of a subgroup of 12,646 participants with self-reported physician-diagnosed hypertension also reported taking antihypertensive medications, thus indicating a reasonable validity of this self-reported diagnosis. 64 Fourth, we did not have any measure of kidney function at baseline and were unable to study the association in those with and without existing CKD separately. Finally, due to the nature of observational studies, causality should be made with caution.…”
Section: Discussionmentioning
confidence: 99%